Shoot and pod diseases of cowpea induced by fungi and bacteria - Emechebe, A.; Florini, D. (1997)
This paper presents a global perspective on bacterial and fungal pathogens that directly infect cowpea foliage, stems, and pods. A brief outline is presented of the main symptoms, distribution, economic importance, epidemiology, and control of bacterial blight/pustule and of 11 fungal diseases: anthracnose, Ascochyta blight, black leaf spot (= leaf smut), brown blotch, brown rust. Cercospora and Pseudocercospora leaf spols. powdery mildew. Pythium soft stem rot. Septoria leaf spot. Sphaceloma scab, and web blight. Minor diseases are listed in a Table.